(untitled) - Kelley, Al (Menlo Park,Calif., 1988)
This book assumes no programming background and can be used by students and first time computer users. For students use, it is intended as a first course in programming.
Keywords: C (Computer program language),C (Ngôn ngữ lập trình máy tính)